2014
DOI: 10.1186/1471-2202-15-100
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone pathways signaling for cell proliferation and survival in hippocampal neural precursors from postnatal mice

Abstract: BackgroundAccumulating evidence suggests that growth hormone (GH) may play a major role in the regulation of postnatal neurogenesis, thus supporting the possibility that it may be also involved in promoting brain repair after brain injury. In order to gain further insight on this possibility, in this study we have investigated the pathways signaling the effect of GH treatment on the proliferation and survival of hippocampal subgranular zone (SGZ)-derived neurospheres.ResultsOur results demonstrate that GH trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…In keeping with previous reports in hippocampal neural precursors [24], GH elicited the activation of both PI3K-Akt and ERK signaling pathways (Figure 4B) that was prevented using selective inhibitors (Figure 4D,E). As also occurred when we investigated the effect of combined administration of GPE and GH on cell proliferation and migration, no differences were observed on either Akt or ERK phosphorylation when both drugs were given simultaneously, as compared with their independent effects (Figure 4C).…”
Section: Resultssupporting
confidence: 92%
“…In keeping with previous reports in hippocampal neural precursors [24], GH elicited the activation of both PI3K-Akt and ERK signaling pathways (Figure 4B) that was prevented using selective inhibitors (Figure 4D,E). As also occurred when we investigated the effect of combined administration of GPE and GH on cell proliferation and migration, no differences were observed on either Akt or ERK phosphorylation when both drugs were given simultaneously, as compared with their independent effects (Figure 4C).…”
Section: Resultssupporting
confidence: 92%
“…Blackmore and his colleagues showed that a seven-day intracerebroventricular infusion of GH increases neural stem cell numbers and augments neurogenesis activity in vitro 35 . Furthermore, GH treatment promotes the proliferation and survival of hippocampal progenitors 21 . Lynch and his colleagues determined that IGF-1 infusion in the right lateral ventricle for 14 days ameliorates age deficits in local cerebral glucose utilization, a function believed to be correlated with neuronal activity 36 and cerebral blood flow 13,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mechanisms of improved cognitive functions after GH treatment are not known but may be due to the direct impact of the hormone on the brain. Observations have indicated that hormones may cross the blood-brain barrier and have confirmed the existence of GH receptors on neural stem and progenitor cells through immunoreactivity studies of GH and its receptors in the various brain areas (especially regions involved in postnatal neurogenesis such as neurospheres derived from the hippocampus) 16,17,18,19,20,21 . Growth hormone treatment has been shown to promote proliferation, differentiation and survival of these neural stem cells 21 .…”
mentioning
confidence: 91%
“…Three themes arise from our genomic data that surgery induces an alteration in endothelial function (thrombin, aldosterone, ERK-5 and eNOS signalling) [24, 30, 3743], inflammation (B-cell receptor, GABA-A and iCOS-iCOSL T-helper cell signalling) [35, 36, 44] and neural plasticity (axonal, GABA A and growth hormone signalling) [31, 34, 45, 46, 48, 50]. Developmentally inappropriate perturbations to any of these processes have the potential to contribute to the development of adverse neural and cognitive development.…”
Section: Discussionmentioning
confidence: 99%